2016
DOI: 10.1007/s40953-016-0064-1
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Turkey’s Credit Ratings with Multivariate Grey Model and Grey Relational Analysis

Abstract: The concept of credit rating rooted back to mid-nineteenth century has become one of the most important elements in the world economy together with the globalization period gradually accelerating in the last two decades and increasing the interaction and sensitivity in the international markets. With the globalization and deepening in the financial markets; the effect, reliability and stability of knowledge of the actors who are in charge for directing the global capital flows have quite a big importance in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In recent years, great attention has been devoted to optimizing and expanding applications of MGM(1, ) model [33][34][35][36][37][38]. Xiong et al [33] provided background values to improve the original MGM model, which can be used to eliminate the random fluctuations and errors of the observational data.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, great attention has been devoted to optimizing and expanding applications of MGM(1, ) model [33][34][35][36][37][38]. Xiong et al [33] provided background values to improve the original MGM model, which can be used to eliminate the random fluctuations and errors of the observational data.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Guo et al [37] constructed SMGM through coupling self-memory principle of dynamic system to MGM; the example showed that SMGM had superior predictive performance over other traditional grey prediction models. Karaaslan andzden [38] analyzed Turkey's ratings credit by multivariable grey prediction model and expanded the application scope of multivariable grey prediction model. Those studies illustrated that multivariable grey prediction model is widely used in many fields.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%